2018
DOI: 10.1111/jmcb.12580
|View full text |Cite
|
Sign up to set email alerts
|

International Business Cycle and Financial Intermediation

Abstract: The paper extends a standard two-country international real business cycle model to include …nancial intermediation by banks of loans and government bonds. Taking in household deposits from home and abroad, the loans are produced by the bank in a Cobb-Douglas production approach such that a bank productivity shock can explain …nancial data moments. The paper contributes an explanation, for both the US relative to the Euro-area, and the US relative to China, of cross-country correlations of loan rates, deposit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Using an open-economy structural VAR, Klug, Mayer and Schuler (2022) find that investment shocks are one of the main drivers of the cyclical component in the current account, with labour market shocks and world demand shocks also playing a dominant role. To model the euro area economy it is essential to devise an open-economy macro-type model as highlighted in the international business cycle literature, pioneered by Benigno (2009), Gali and Monacelli (2005) and Gillman et al (2018). For our purposes this is even more important, as the current account is one of the main channels for transmitting foreign shocks.…”
Section: Related Literaturementioning
confidence: 99%
“…Using an open-economy structural VAR, Klug, Mayer and Schuler (2022) find that investment shocks are one of the main drivers of the cyclical component in the current account, with labour market shocks and world demand shocks also playing a dominant role. To model the euro area economy it is essential to devise an open-economy macro-type model as highlighted in the international business cycle literature, pioneered by Benigno (2009), Gali and Monacelli (2005) and Gillman et al (2018). For our purposes this is even more important, as the current account is one of the main channels for transmitting foreign shocks.…”
Section: Related Literaturementioning
confidence: 99%
“…Moreover, a two-country, two-sector international RBC model with investment and consumption goods sectors was developed with investment-specific technology shocks and used for an analysis of the volatility of the business cycle in emerging markets (Dogan 2019). At the same time, the two-countries RBC model was used to explain cross-country correlations between the loan rates, deposit rates, and loan premiums for both the United States relative to the Euro-area and the United States relative to China (Csabafi et al 2019). Also, a medium-scale open-economy DSGE model was used for a comparative analysis of the volatility of Ethiopia's business cycle under interest rate and money growth rules, where it was found that the model with the money growth rule was essentially less powerful for the transmission of exogenous shocks originating from government spending programs, monetary policy, technological progress, and exchange rate movements (Melesse 2019).…”
Section: Literature Reviewmentioning
confidence: 99%